Pentingnya Sistem Kekebalan Tubuh (Imunisasi) Pada Balita Dalam Membangun Pertahanan Yang Diperlukan Untuk Melawan Infeksi Dan Penyakit - Jannah, Raudatul; Hajrah, Fifit; K, Fitriani; Wahyuni, Sri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Immunization is an effort to actively create/increase a person's immunity to a disease so that if one day they are exposed to the disease they will not get sick or only experience mild illness. The purpose of Community Service is to provide information to the community about the importance of complete basic immunization for infants and toddlers in reducing morbidity and mortality due to diseases that can be prevented by immunization and to find out the understanding of mothers about complete basic immunization in infants by conducting pretests and posttests. The method used in Community Service activities is health education about complete basic immunization which is carried out directly by the PkM TEAM. The results of community service obtained that this activity ran smoothly and in accordance with the program of activities by the PkM TEAM. The conclusion is that to overcome the occurrence of dangerous diseases in children, of course there are many things that can be done, namely providing complete immunization, but family support and maternal compliance in carrying out immunization are very much needed.